2012
DOI: 10.5152/akd.2012.003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and hemodynamic features of Eisenmenger syndrome patients at the time of first admission: a tertiary referral-center experience

Abstract: Bu çalışmanın özeti, 21-24 Mayıs 2011 tarihlerinde Gothenburg -Sweden'da yapılan ESC Heart Failure Kongresi'nde poster bildirisi olarak sunulmuştur. ABSTRACTObjective: In this study, patients admitted with the diagnosis of Eisenmenger syndrome (ES) in a tertiary referral center were analyzed. Methods: The data of 20 consecutive patients (mean age: 27.6+1.8 years, 7 male and mean follow-up time: 35.6±9.1 months) with ES were retrospectively analyzed. Demographic characteristics, symptoms, physical examination,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
1
1
Order By: Relevance
“…In our study, the mean 6MWT was 218.75 meters ± 65.58 (range 120-340) in adult patients with Eisenmenger syndrome This was lower than a study conducted by Güngör et al who reported that mean 6MWD was 347 meters in patients with Eisenmenger syndrome (10) . This was lower also form the mean 6MWT from REHAB registry which was 370.0 meters (280.0-451.5) (6) .…”
Section: Mwt In Functional Assessment Of Patients With Pulmonary Hypcontrasting
confidence: 80%
“…In our study, the mean 6MWT was 218.75 meters ± 65.58 (range 120-340) in adult patients with Eisenmenger syndrome This was lower than a study conducted by Güngör et al who reported that mean 6MWD was 347 meters in patients with Eisenmenger syndrome (10) . This was lower also form the mean 6MWT from REHAB registry which was 370.0 meters (280.0-451.5) (6) .…”
Section: Mwt In Functional Assessment Of Patients With Pulmonary Hypcontrasting
confidence: 80%
“…In a study from Turkey, the mean 6MWD was found to be 184 m with the highest values (201 m) observed in the patient group with PAH associated with congenital heart disease and the lowest value (159 m) observed in the patient group in PAH associated with connective tissue diseases ( 16 ). In another study, Güngör et al ( 17 ) reported that mean 6MWD was 347 m in patients with Eisenmenger syndrome.…”
Section: Introductionmentioning
confidence: 95%